Perbandingan Teknik Penerjemahan dan Analisis Komponen Makna Penerjemahan Komik Magic Kaito Volume 1-4 Karya Aoyama Gosho - Mahatma Suputra, I Gede Putu (Humanis, 2017)
This research aimed to examine translation technique and component of meaning analysis of same words in source text that are translated in different word by two different translators in  1-4 volume of Magic Kaito comics by Aoyama Gosho. The data were analysed using descriptive method. This research used the theory of translation technique by Molina and Albir (2002) and theory of component of meaning by Nida and Taber (1969). From 14 data, there are seven data that used same translation technique and  seven data that used different translation technique. Based on component of meaning analysis, The first translator produces a better translation than the second translator, because the first translator produces translations with meaning that is closer to source text than the second translator.
Keywords: comparative translation, translation technique, component of meaning